Reliability Assessment of Smart Grids Considering Indirect Cyber-Power Interdependencies - Falahati, Bamdad; Yong Fu (IEEE transactions on smart grid, 2014)
The operation of power systems now relies on extensive applications of digital communication systems, known as cyber networks. These applications are categorized as having either direct or indirect interactions between cyber and power networks. We previously studied direct interdependencies inside cyber-power networks and proposed the state mapping based model to evaluate its impact on the power system reliability. This paper focuses on indirect interdependencies between cyber and power networks. Certain applications of indirect interdependencies in modern power systems are discussed, and a state updating-based model is proposed to quantitatively evaluate the reliability of cyber-power networks under indirect interdependencies. Two optimization models are used to maximize the data connectivity in the cyber network and minimize the load curtailment in the power network. A high-voltage substation equipped with both monitoring and protection systems is studied to show the effectiveness of the proposed solution model.